Possibilities of swimming skills developing in the process of physical education and sports at high school students taking into account gender differences. - Ganchar A.I (Kharkov National Pedagogical University, 2011)
The aim of an article: to reveal level and degree of swimming skills development at male and female cadets by the level of swimming skills they have attained in the course of physical training and sports. Article discusses divergent possibilities of freestyle swimming skills development at the representatives of different gender cadets depending on their initial level and degree of swimming readiness on the basis of different quantity of visited obligatory and facultative studies during 1st-2nd years of professional education.